2014
DOI: 10.1128/iai.01340-13
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Strains Lacking Surface Lipid Phthiocerol Dimycocerosate Are Susceptible to Killing by an Early Innate Host Response

Abstract: The innate immune response plays an important but unknown role in host defense against Mycobacterium tuberculosis. To define the function of innate immunity during tuberculosis, we evaluated M. tuberculosis replication dynamics during murine infection. Our data show that the early pulmonary innate immune response limits M. tuberculosis replication in a MyD88-dependent manner. Strikingly, we found that little M. tuberculosis cell death occurs during the first 2 weeks of infection. In contrast, M. tuberculosis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 43 publications
0
51
1
Order By: Relevance
“…For analysis of PDIM lipids, 6 l of each M. marinum lipid sample was resolved on a 12-cm by 9-cm TLC silica gel 60 plate (Merck KGaA, Darmstadt, Germany) using low-boiling-point petroleum ether-ethyl acetate (50:1; Fisher Scientific) for ϳ28 min (82). The following reagent was obtained through BEI Resources, NIAID, NIH: Mycobacterium tuberculosis strain H37Rv purified phthiocerol dimycocerosate (PDIM; catalog number NR-20328).…”
Section: Methodsmentioning
confidence: 99%
“…For analysis of PDIM lipids, 6 l of each M. marinum lipid sample was resolved on a 12-cm by 9-cm TLC silica gel 60 plate (Merck KGaA, Darmstadt, Germany) using low-boiling-point petroleum ether-ethyl acetate (50:1; Fisher Scientific) for ϳ28 min (82). The following reagent was obtained through BEI Resources, NIAID, NIH: Mycobacterium tuberculosis strain H37Rv purified phthiocerol dimycocerosate (PDIM; catalog number NR-20328).…”
Section: Methodsmentioning
confidence: 99%
“…One of these reductases (Ddn, encoded by the Rv3547 ORF) acts as a nitroreductase to activate a prodrug called PA-824, a promising anti-TB drug that acts in concert with F 420 H 2 (45,60,63,64). The hydroxymycolic acid dehydrogenase (fHMAD), which generates ketomycolic acids (K-MA) from hydroxymycolic acids (H-MA), and fPKR studied here exemplify the critical role of F 420 in the functionalization of the formidable cell wall lipids that protect M. tuberculosis from the host immune attack and from anti-TB drugs (12,39,61,(65)(66)(67)(68)(69)(70). Also, fHMAD is one of the targets of PA-824 (39).…”
Section: Figmentioning
confidence: 99%
“…The pathways for the biosynthesis of DPs are of great interest because these compounds are virulence factors for Mycobacterium tuberculosis and Mycobacterium leprae, which cause tuberculosis (TB) and leprosy, respectively (3)(4)(5)(6)(7)(8)(9)(10)(11). It was recently shown that these polyketide derivatives protect M. tuberculosis from the early innate immune response of an infected host (12). The DPs are generated by esterifying ␤-glycol-containing long-chain polyketides (PK) with long-chain multimethyl-branched fatty acids ( Fig.…”
mentioning
confidence: 99%
“…Moreover, the PDIM lipids have been recently implicated in host immune evasion by masking pathogen–associated molecule patterns (PAMPs), and the absence of PDIMs promoted the recruitment of macrophages producing reactive nitrogen species (Cambier et al, 2014). However, another study showed that the attenuation of PDIM-deficient M. tuberculosis strain is RNIs independent (Day et al, 2014), indicating some controversy in the role of PDIM in the protection of mycobacteria from host-mediated killing.…”
Section: Discussionmentioning
confidence: 99%